Підходи до стратегічного забування: дослідження та порівняльний аналіз - Бондарчук, А. С. (ХНУРЕ, 2019)
This work is dedicated to researching the modern concept of strategical forgetting. Nowadays, in the technological century, the AI systems grow faster and faster, learn more and more information day by day. Actually, there is no such huge memory space for storing all information needed for all-knowing systems. Even if scientists discover some, will it be efficient? Therefore, even despite a variety of disadvantages and problems, this is a huge importance of discovering the reason why forgetting is totally needful and what is the best way to filter an input information to make the system forget strategically